UPAYA MENINGKATKAN HASIL BELAJAR SISWA MELALUI METODE PERMAINAN SHOOT THEM UP PADA MATA PELAJARAN BAHASA INGGRIS - Muhaya, Aay; Kamal, Mustopa (Bestari, 2019)
This research is motivated by the low motivation and value of students in learning English which is caused by several factors, one of which is the lack of variations in learning methods, so far dominated by teachers (teacher centered) making students passive, less interested in learning, bored and not paying attention to the teacher, students are less involved in learning activities so students lack enthusiasm for learning, learning is not packaged in the form of games that attract students' attention, therefore researchers choose the method of shooting them up. Them up shoot game method places students to master the material through game-based learning. Starting from the above, the researcher formulated three main problems, namely: 1) How is the preparation of the English learning plan (RPP) using the game shoot them up? Method; 2) What is the process of implementing English learning by using the game shoot them up method ?; 3) How to improve student learning outcomes in English lessons using the game shoot them up method? The purpose of this study are: 1) To find out the preparation of learning plans (RPP) in English by using the method of shooting them up; 2) To find out the process of implementing English learning by using the game shoot them up method; 3) To find out the improvement in student learning outcomes in English subjects by using the game shoot them up method. The research method used by the author is the Kemmis model class action research (CAR) method and Taggart MC. This research is a cycle model that is carried out repeatedly and continuously, namely the cycle to achieve increased results. This cycle consists of several stages, namely class action planning, action, observation, and reflection. While the data collection techniques used are observation and technical test techniques. After conducting research in the fourth grade of SDN 1 Ciharalang, the researchers obtained the following conclusions: 1) The teacher experienced an increase in the ability to prepare lesson plans using the method of shooting them up on English subjects, it can be seen from the results of the first cycle 87,584, cycle II 89,666 and cycle III 91,434; 2) Teachers experience increased ability to carry out the learning process using the method of shooting them up on English subjects, it can be seen from the results of the first cycle of research 85.87, cycle II 88.11 and cycle III 90.14; 3) Student learning outcomes using the method of shooting them up on English subjects has increased, it can be seen from the results of student tests with an average value that is pre cycle 67.08, cycle I 72.34, cycle II 90, 21 and cycle III 90.87. Thus, the use of shoot them up method on English subjects can improve student learning outcomes.